Zakat Distribution For Productive Student Scholarship Program By BAZNAS Gresik Regency In Yusuf Al-Qardhawi’s Perspective - Pratiwi, Retno Dini (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
BAZNAS is the official and only institution formed by Indonesian government have an important role in the utilization of zakat. As a form of concern for deserver of zakat in education especially in the Gresik Regency area, BAZNAS Gresik Regency established a program called Productive Student Scholarship. Yusuf Al-Qardhawi as a contemporary fiqh scholar, has a thought about zakat which is moderate and can be implemented in this era. In this study, the Productive Student Scholarship Program by BAZNAS Gresik Regency is linked to the perspective of Yusuf Al-Qardhawi. The purpose is to explain and analyze Productive Student Scholarship program at BAZNAS Gresik analyzed from Qardhawi's perspective. This research uses empirical research using a qualitative approach. Sources of data used are primary and secondary data with data collection methods through interviews. The result of this study are The Productive Student Scholarship Program is part of one of the pillars of the